HIDRADENITIS SUPPURATIVA: A RETROSPECTIVE REVIEW OF 13 PATIENTS AND LITERATURE SUMMARY - Reneeka Persaud; James A. Elliott; Laurie Goodman; Ranjani Somayaji; Morgan Lim; Gary Sibbald (European Medical Journal, 2017)
Hidradenitis suppurativa (HS) is an inflammatory skin condition of the follicular pilosebaceous unit that primarily affects flexural areas where apocrine glands are found. This disorder can present as either an acute or chronic disease, with a single subcutaneous nodule or clusters of painful abscesses with purulent drainage in one or more of the following sites: axilla, groin, genital, perianal (more common in males), and under the breasts (more common in females). Over time patients form sinus tracts, fibrosis, and scarring. The onset usually occurs in the early 20s, after puberty. HS can be present for years without being diagnosed and is associated with a diminished quality of life, high morbidity, and substantial healthcare costs. Global HS prevalence is estimated at 1%. This article reviews a retrospective cohort study of 13 patients assessed by an interprofessional wound care team and discusses relevant literature. Accuracy of referral diagnosis was the primary outcome. Secondary outcomes included demographics and quality of life. In total, 10 patients were female (77%) and the mean age was 33 years. Fewer than half (n=6, 46%) had an accurate diagnosis of HS prior to team assessment. Of these patients, the mean time before a correct diagnosis was 4.2 years. Untreated bacterial damage was diagnosed in the majority of patients (n=9, 69%). There was substantial improvement in pain levels and quality of life in approximately half of the cases. Over time, patients became more actively involved in their care. Our findings show HS diagnosis and management is optimised with an interprofessional team approach.